Social Panorama of Latin America 1996 - United Nations (United Nations, 1996)
In addition to dealing with core issues such as children and the family, this publication shows trends in the early 1990s in important facets of social development such as poverty, income distribution, employment, social expenditure, education and pay levels. The analysis is complemented by numerous statistical tables.